Build a scale to measure speed of strategic thinking for young footballers - AlKhokhy, Firas Mahmood Ali; AlHilaly, Ahmed Hisham Ahmed; Tobail, Ali Hussein Mohammed (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Soccer has gained global attention from both men and women. However, the lack of a perfect objective scientific scale to measure strategic thinking speed is the main reason. This study aims to develop a scale to measure the strategic thinking speed of young soccer players. The study also aims to understand their level of strategic thinking speed and to establish value and level standards to measure the strategic thinking speed of young soccer players. Material and Methods. This study uses a descriptive-correlational method with the aim of constructing and validating the scale. The research population consisted of 169 young soccer players (aged 16-18 years) in Mosul City for the 2024-2025 soccer season who were registered in 7 clubs in Nineveh, Mosul, Al-Mustakbal, Al-Omal, Al-Futowa, Al-Amwaj, and AlHadbaa. The main research sample, after excluding (14) goalkeepers, amounted to (155) representing (91.71%) of the total population. The instruments used in this study were questionnaires, interviews, analysis, references, and resources. The researchers applied the scale to the sample by coaches and expert staff. The analysis was assisted using the SPSS 26 application. Results. Based on the results of the study, it was revealed that the developed scale significantly measures strategic thinking speed among young soccer players. The results of the study also show that the significance value (0.000